Appraising road safety attainment by CRITIC-ELECTRE-FCM: A policymaking support for Southeast Asia. (June 2022) - Chen, Faan; Zhu, Yilin; Zu, Jiacheng; Lyu, Jingyang; Yang, Junfeng
Abstract: Road traffic crashes have been a leading cause of death in Southeast Asian countries, which greatly harms the development of countries and affects the livelihood of countless families in this region. In this context, a regular review of road safety attainment is needed to understand why road crashes happen and to better guide the ongoing policymaking and implementation of effective countermeasures as well as next-level strategies. This study introduces an easy-to-use, effective, and systematic methodology for multi-criteria decision-making, CRiteria Importance Through Inter-criteria Correlation (CRITIC) - ELimination and Et Choice Translating REality (ELECTRE) - Fuzzy C-Means (FCM) (CRITIC-ELECTRE-FCM). Its purpose is to appraise the road safety attainment of 11 countries in Southeast Asia. Accompanied by the robustness of analyses with other widely used methods, these countries are ranked and grouped into several levels regarding their road safety attainment over the past decade (2009–2018). The findings provide government officials, policymakers, and any stakeholders of these countries with meaningful information (e.g., what has been done well and what has not) and instructive guidance for future action. Overall, the proposed appraisal system serves as an efficacious policymaking support for countries in the region to review road safety attainment, develop future strategies and policies, and implement safety management. Highlights: Examine road safety attainment across Southeast Asian countries. Offer a practical paradigm to chart future strategic directions. Define ways to accelerate action on proven policies. Provide meaningful guidance for future action for Southeast Asia. Extend the existing policymaking support system for road safety cases.